2006
DOI: 10.1007/s00220-006-0043-z
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Quantization, Parallel Transport and the Fourier Transform

Abstract: In quantum mechanics, the momentum space and position space wave functions are related by the Fourier transform. We investigate how the Fourier transform arises in the context of geometric quantization. We consider a Hilbert space bundle H over the space J of compatible complex structures on a symplectic vector space. This bundle is equipped with a projectively flat connection. We show that parallel transport along a geodesic in the bundle H → J is a rescaled orthogonal projection or Bogoliubov transformation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(72 citation statements)
references
References 11 publications
1
71
0
Order By: Relevance
“…In the second case, the need for half-forms is less evident. Nonetheless, it is commonly believed that the half-form correction is necessary also in the Kähler case and many arguments have been presented in its favor: the half-form correction renders the BKS pairing map unitary in the quantization of vector spaces with translation invariant complex structures [ADW91,KW06] and of Abelian varieties [BMN10] and allows for a transparent explanation of the vacuum energy shift in the Kähler quantization of symplectic toric varieties with toric Kähler structures [KMN10].…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second case, the need for half-forms is less evident. Nonetheless, it is commonly believed that the half-form correction is necessary also in the Kähler case and many arguments have been presented in its favor: the half-form correction renders the BKS pairing map unitary in the quantization of vector spaces with translation invariant complex structures [ADW91,KW06] and of Abelian varieties [BMN10] and allows for a transparent explanation of the vacuum energy shift in the Kähler quantization of symplectic toric varieties with toric Kähler structures [KMN10].…”
Section: Preliminariesmentioning
confidence: 99%
“…This bundle has a natural connection (generalizing the connections of Axelrod-Della Pietra-Witten [ADW91] and Hitchin [Hit90]) which is given by projecting the trivial connection in the trivial bundle whose fiber is the space of all square-integrable sections of the prequantum line bundle onto the almost-holomorphic subbundle. In the case that the symplectic manifold is a symplectic vector space and one restricts to translation invariant complex structures, this connection is known to be projectively flat [ADW91,KW06]. On the other hand, if one considers the full family of almost complex structures, Foth and Uribe have shown that the connection is never projectively flat, even semiclassically [FU07].…”
Section: Introductionmentioning
confidence: 99%
“…The real Lagrangian subspaces are on the boundary (at infinity) of the space of complex structures. When the geodesic is extended to infinity, the parallel transport yields the Segal-Bargmann and Fourier transforms (see [8]). …”
Section: Introductionmentioning
confidence: 99%
“…The rest of the topological boundary consists of polarisations that are partly real and partly complex. For any J 0 ∈ J ω and L ∈ L ω , there is a geodesic {J t } in J ω from J 0 such that lim t→+∞ J t = L. We have [5] Geometric phases in quantisations 225 (see [8] for half-form quantisation. The result for half-density quantisation is then straightforward).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation